The relationship between education, land, labor and agriculture output in Malaysia - Heng, Sze Woon (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study examines whether relationship exists between education, land, labor and agriculture output in Malaysia over 33 years period starting from year 1980 to 2012. The estimation has been conducted to examine whether there is any cointegration and/or causality relationship between education, land, labor and agriculture output. Unit Root test, Johansen-Juselius Cointegration test, and VAR Granger Causality are employed in this study. The empirical results shows that all the variables are stationary atfter first differencing and are integrated of order one, I(1). Although there is no existence of cointegration, unidirectional causality relationship does exist between education, land, labor and agriculture output. The causality relationships are running from all the independent variables which are education (LEDUEX), land (AGLN) and labor (EMPAG) towards the dependant variable, agriculture output (LAVA). Besides that, there is also causality relationship running from AGLN towards EMPAG.